Risk factors associated with gastrointestinal dysfunction in horses undergoing elective procedures under general anaesthesia. (December 2013) - Nelson, B. B.; Lordan, E. E.; Hassel, D. M.
Summary: Reasons for performing study: Gastrointestinal dysfunction occurs commonly following elective anaesthesia. Identification of risk factors may allow implementation of preventative measures to reduce the prevalence of colic following elective anaesthetic procedures. Objectives: To examine risk factors associated with gastrointestinal dysfunction or post anaesthetic colic for horses undergoing elective surgical or diagnostic procedures under general anaesthesia. Study design: Retrospective case series. Methods: Medical records were collected from adult horses undergoing general anaesthesia from 1 January 2008 to 31 December 2010 using a retrospective cohort design. Potential risk factors were examined using univariable logistic regression with a limit of a P<0.25. Through backward elimination, the final multivariate model was created to identify variables significantly associated with gastrointestinal dysfunction. Results: Colic or delayed faecal output was reported in 36 out of 416 (8.7%) horses undergoing general anaesthesia in the study period. In the final multivariable model, horse breed (P = 0.05), intraoperative peripheral blood lactate (P = 0.02), right lateral recumbency during general anaesthesia (P = 0.04), post anaesthetic rectal temperature (P = 0.03) and hours to first passage of faeces (P<0.01) were statistically significant between horses that exhibited colic compared with those that did not. Arabians were more likely to develop colic compared with other horse breeds (4/13, 30.8%). Horses that exhibited gastrointestinal dysfunction passed faeces later than those that did not (7.2 ± 0.8 h and 5.4 ± 0.2 h, respectively). As blood lactate increased at the end of anaesthesia, the odds of colic occurring also increased (odds ratio:1.4, 95% confidence interval: 1.04–1.83, P = 0.02). Conclusions: This study demonstrated the prevalence of colic in horses undergoing elective general anaesthetic procedures in our hospital population. Arabian horses, increasing blood lactate and delayed passage of faeces were significantly associated with an increased risk of gastrointestinal dysfunction.